THE INFLUENCE OF STUDENT ENGAGEMENT AND CRITICAL THINKING ON STUDENT ENGLISH LEARNING - Fadilah, Lafiyati; Suryadi, Suryadi (TELL - US JOURNAL, 2025)
The capacity to communicate in English has become essential for pupils worldwide in the context of contemporary education. this study is to investigate how students' critical thinking and engagement affect their achievement and level of interest in learning English. Using aquantiative methodology, there were 360 pupils enrolled at SMPN 10 Kota Serang when this study was carried out. Purposive sampling was used to choose 108 student from this demographic as a sample. The research's principal instrument was a paper-based questionnaire that was methodically created to gauge three important criteria. The result initiatives to enhance English learning outcomes in middle school settings should prioritise raising student engagement. This study's main finding is that internal student factors have a significant impact on English learning outcomes, which are not only dictated by external teaching approaches.